2020
DOI: 10.1126/science.abd4250
|View full text |Cite
|
Sign up to set email alerts
|

Viral epitope profiling of COVID-19 patients reveals cross-reactivity and correlates of severity

Abstract: Understanding humoral responses to SARS-CoV-2 is critical for improving diagnostics, therapeutics, and vaccines. Deep serological profiling of 232 COVID-19 patients and 190 pre-COVID-19 era controls using VirScan revealed over 800 epitopes in the SARS-CoV-2 proteome, including 10 epitopes likely recognized by neutralizing antibodies. Pre-existing antibodies in controls recognized SARS-CoV-2 ORF1, while only COVID-19 patients primarily recognized spike and nucleoprotein. A machine learning model trained on VirS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
802
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(898 citation statements)
references
References 39 publications
87
802
7
2
Order By: Relevance
“…2A). As IgG and IgA are the most abundant isotypes in blood 53 APGQTGKIADYNYKLPDDFT' for horse (Fig. 3A); 'YQPYRVVVLSFELLH' and 'CVNFNFNGL' for mouse (Fig.…”
Section: Characterization Of the 18 Linear B-cell Epitopes Selected Wmentioning
confidence: 99%
“…2A). As IgG and IgA are the most abundant isotypes in blood 53 APGQTGKIADYNYKLPDDFT' for horse (Fig. 3A); 'YQPYRVVVLSFELLH' and 'CVNFNFNGL' for mouse (Fig.…”
Section: Characterization Of the 18 Linear B-cell Epitopes Selected Wmentioning
confidence: 99%
“…T14I mutation is also present in peptides predicted as HLA Class I T cell epitopes. 12 M: D3G and N: S194L mutations are present in antibody epitopes, 16 which may reduce antibody avidity. Mutation effects can contribute to immunomodulation that increases CFR, because innate immune system depression, 37 adaptive immune system dysregulation, 38 and incoordination between cell-mediated and humoral immunity 39 underlie the exacerbation of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found that mutations associated with higher prevalence, such as ORF1a: I300F (nsp2), ORF1a: H1113Y (nsp3), ORF1b: A1844V (nsp14), S: T307I; ORF6: I33T, N: A12G/ORF9b: H9D, N: S197L, and N: A220V, are present in antibody epitopes. 16 ORF6: I33T is also located in a HLA-DR T cell epitope. 36 The high prevalence among NHB and Hispanics has been attributed to living in densely populated areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has revealed that even people who have not been infected with the virus can have antibodies 3 and T cells 2 that recognize SARS-CoV-2. This might be the result of people having previously been infected with related coronaviruses that cause the common cold.…”
Section: The Immunity Challengementioning
confidence: 99%